Comparative gas exchange performance during the wet season of three Brazilian Styrax species under habitat conditions of cerrado vegetation types differing in soil water availability and crown density - Habermann, Gustavo [UNESP]; Ellsworth, Patricia F. V.; Cazoto, Juliana L.; Simao, Edson [UNESP]; Bieras, Angela C. [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2011)
We studied the influence of environmental conditions in different vegetation types of the Brazilian savanna (cerrado s.l.) on CO2 assimilation and water use efficiency of Styrax ferrugineus, S. camporum and S. pohlii, which are morphologically similar but have distinct distribution patterns. We measured leaf gas exchange and water relations in adult and young plants. Adult plants of S. ferrugineus were measured in the cerrado s. str.: plants of S. camporum at the edge of cerradao, a woodland vegetation; and in a riparian forest those of S. pohlii. Eight-month-old young plants were planted in the cerrado s. str., at the edge and in the understory of the cerradao, and in the understory of the riparian forest. For young plants, the high light availability in the cerrado s. str. resulted in a threefold greater CO2 assimilation rate (A) compared to the other sites. A of adult plants under full irradiation (1800 mu mol photons m(-2) s(-1)) was significantly lower in S. pohlii compared to S. ferrugineus and S. camporum. Although sufficient soil water was available at every site at the end of the wet season, the extreme high water content in the riparian forest soil led to increased stomatal conductance (gs) and transpiration rate (E) for young plants of S. camporum and S. pohlii, but not of S. ferrugineus. However, the large gs in S. pohlii and S. camporum young plants did not result in higher A rates. The differences may indicate some specialization of S. ferrugineus to best growth in open savanna and of S. pohlii in riparian forest habitats. The high water use efficiency of S. camporum young plants in the understory of cerradao seems not yet sufficient to emphasize that this species benefits from this particular habitat. Because, while water supply during the wet season is quite sufficient, soil water deficits and frequent fires can occur during the dry season and might modify strongly the habitat conditions for the three Styrax species. (C) 2010 Elsevier GmbH. All rights reserved.
Keywords: Cerrado woody species; Net photosynthesis; Gas exchange; Water relations; Styracaceae